Correlation between Physical Character of Seeds and Germination of Sunflower Seeds (Helianthus annuus L.) - Astutik, Fina Dian; Ardiarini, Noer Rahmi (Department of Agronomy, Faculty of Agriculture, Brawijaya University, 2024)
Sunflower (Helianthus annuus L.) it has high economic potential as a raw material for the food industry and is extracted to produce vegetable oil. The high use of sunflowers causes this plant to be widely cultivated around the world, including in Indonesia. Sunflower production in Indonesia is not enough to meet market needs due to low knowledge related to seed quality. Quality seeds of appropriate size can affect germination and plant growth character. The purpose of this study is to determine the relationship between physical quality and physical character of seeds on the germination of sunflower seeds. The research activity was carried out at the Plant Breeding Laboratory, Faculty of Agriculture, University of Brawijaya Malang in the month of Mare-June 2024. The research was conducted using observation and measurement methods. The variables observed were seed length, seed width, seed thickness, weight of 1000 seeds, seed moisture content, germination power, maximum growth potential, vigor index, growth speed, growth synchronicity, plumula and radicle length. This study uses the analysis of diversity coefficient and correlation coefficient. The results showed that the physical character of sunflower seeds between genotypes had medium diversity and within genotypes had low to high diversity. Physical quality characteristics and physical characteristics of seeds between size groups regardless of genotype, between genotypes, and in genotypes have a positive correlation for all germination characteristics. The improvement in physical quality and seed size was followed by an increase in germination characteristics. Large seeds have a larger embryo size and food reserves as well as enough nutrients to support embryonic development during the germination phase.